Association Analysis with Apriori Algorithm for Electronic Sales Decision Support System - Syafariani, R. Fenny (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2022)
The purpose of this study was to determine the level of dependence of various items in order to dig up information on what items are dependent on other items. The method used in this research is descriptive analysis with a qualitative approach through a priori algorithm. The results show that the association analysis of the 26 transactions taken is 76.47%. A consumer who buys a laptop electronic device has the possibility to also buy an electronic mouse